2016
DOI: 10.3168/jds.2016-10905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3 sequestering agents on milk aflatoxin M1 concentration and the performance and immune status of dairy cows fed diets artificially contaminated with aflatoxin B1

Abstract: This study examined whether adding 3 mycotoxin-sequestering agents to diets contaminated with aflatoxin B1 (AFB1) would reduce milk aflatoxin M1 (AFM1) concentration, and improve the performance and alter immune status of dairy cows. Fifteen lactating dairy cows were used in an experiment with an incomplete crossover design including four 28-d periods. Treatments included a control diet (C), a toxin diet (T; 1,725µg of AFB1/head per day; 75µg/kg), and diets containing the toxin and 20g/head per day of a propri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
45
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 39 publications
16
45
4
2
Order By: Relevance
“…These results suggest that TN and UP did not alter metabolism of absorbed AF to AFM 1 , nor its transfer into, and secretion from, the mammary glands but rather reduced uptake from the gut. This is in agreement with the similar clearance of AFM 1 in the presence or absence of a mycotoxin-sequestering agent found by Queiroz et al (2012) but is in contrast to the study of Ogunade et al (2016), who reported that 3 mycotoxin-sequestering agents evaluated did not reduce AFM 1 concentrations in milk during the dosing period but hastened their decline postdosing.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…These results suggest that TN and UP did not alter metabolism of absorbed AF to AFM 1 , nor its transfer into, and secretion from, the mammary glands but rather reduced uptake from the gut. This is in agreement with the similar clearance of AFM 1 in the presence or absence of a mycotoxin-sequestering agent found by Queiroz et al (2012) but is in contrast to the study of Ogunade et al (2016), who reported that 3 mycotoxin-sequestering agents evaluated did not reduce AFM 1 concentrations in milk during the dosing period but hastened their decline postdosing.…”
Section: Resultssupporting
confidence: 91%
“…As expected, cows fed AF secreted substantial quantities of AFM 1 into their milk. Concentrations of AFM 1 in milk were consistent with those reported by Kutz et al (2009), who also fed AF at about 100 μg/kg of DM, but were markedly higher than those reported by others (Queiroz et al, 2012;Ogunade et al, 2016), who fed about 75 μg of AF/kg of DM, indicating a large difference in absorption, probably due in part to concentrations of AF fed. Inclusion of either TN or UP in the diet significantly reduced (P < 0.01) the concentration and mass of AFM 1 secreted in milk by 50 to 60%, relative to cows on PC treatment, and no statistical difference was observed between TN and UP.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations